위암환자에서 분리된 Helicobacter pylori의 항생물질에 대한 감수성과 저항성 균에 대한 항생제 병합요법의 효과 - 송갑영; 장명웅; Song, Gap-Young; Chang, Myung-Woong (The journal of the Korean Society for Microbiology, 1999)
The purpose of this study was to evaluate the existence of amoxicillin, clarithromycin, and metronidazole resistance Helicobacter pylori and to determine the in-vitro MIC of two and three kinds of antibiotic concominant administration in the isolates. The antimicrobial agents tested against 169 H. pylori included metronidazole, amoxicillin, ciprofloxacin, clarithromycin, omeprazole, josamycin, erythromycin, and tetracycline. MIC of each antimicrobial agents was determined by broth microdilution method. The 169 strains of H. pylori were isolated from biopsy specimens of patients with gastric cancer. $MIC_{50}$ of clarithromycin, amoxicillin, metronidazole, omeprazole, erythromycin, josamycin, tetracycline, and ciprofloxacin was 2.0, 1.0, 4.0, 8.0, 0.5, 0.5, and $0.5\;μg/ml$, respectively. $MIC_{90}$ of clarithromycin, amoxicillin, metronidazole, omeprazole, erythromycin, josamycin, tetracycline, and ciprofloxacin was 64.0, 64.0, 32.0, 16.0, 8.0, 2.0, and $1.0\;μg/ml$, respectively. H. pylori isolates were detected in the following resistaince rates: 34.3% to clarithromycin, 31.9% to metronidazole, 20.7% to amoxicillin, 12.4% to erythromycin, and 10.1% to josamycin. The prevalence of the antibiotic resistant strains of H. pylori were detected 18.1% for two kind of antibiotics and 9.6% for three kind of antibiotics, and 3.9% for four kind of antibiotics. The $MIC_{90}$ of clarithromycin-, metronidazole-, and amoxicillin-resistant H. pylori was decreased under the $1\;μg/ml$ by the two or three kind of antibiotic concomitant administration in-vitro. These results suggest that two or three antibiotics concomitant administration could be more effective for the treatment of clarithromycin-, amoxicillin-, metronidazole-, and josamycin-resistant H. pylori strains.